Representasi Perempuan Pekerja Seks Komersial dalam Serial Kupu-Kupu Malam WeTv berdasarkan Perspektif Teori Pertukaran Sosial - Maulana, -; Komariah, Siti; Wulandari, Puspita (Saskara : Indonesian Journal of Society Studies, 2023)
A film called Night Butterfly produced by MD Pictures presents the realities of women's lives as commercial sex workers. The purpose of this study was to find out how women commercial sex workers were represented in the film Night Butterfly. This research uses Roland Barthles' semiotic analysis model using the approach of social exchange theory. The method used is the analysis of scenes that have symbols, meanings, and messages played by Laura's character in representing women commercial sex workers. The result of this study is to know the social reality of women from the side of sex workers as commodities in the gluttonous capitalist economic machine. In addition, the scenes from the film give a clear picture of the reality and the driving factors for a person to do the work, namely economic factors, so that the assumption is formed that marginalized groups are easier to portray and represent in the form of films, as well as women. Like Laura's character being further marginalized by focusing on sexuality.